2024
DOI: 10.3389/fonc.2023.1329298
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of JAK2-V617 F mutation and BCR::ABL1 translocation in chronic myeloproliferative neoplasms: a potentially confounding genetic combination

Magda Zanelli,
Alessandra Bisagni,
Francesca Sanguedolce
et al.

Abstract: Myeloproliferative neoplasms (MPNs) are classified into Philadelphia (Ph) chromosome–positive chronic myeloid leukemia (CML) and Ph-negative MPNs. BCR::ABL1 translocation is the key genetic event of CML, whereas JAK2/MPL/CALR mutations are molecular aberrations of Ph-negative MPNs. Despite initially considered mutually exclusive genetic aberrations, the co-occurrence of BCR::ABL1 and JAK2 has been reported in a limited number of cases. The two genetic alterations may be identified either at the same time or JA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…BCR::ABL1 rearrangement, at the basis of CML development, and JAK2 mutations were initially considered mutually exclusive genetic alterations. However, since JAK2 first discovery in 2005, an increasing number of patients with concomitant BCR::ABL1 rearrangement and JAK2 mutations have been reported, and in a recent comprehensive review of the literature, we identified 87 cases carrying both genetic abnormalities ( Zanelli et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BCR::ABL1 rearrangement, at the basis of CML development, and JAK2 mutations were initially considered mutually exclusive genetic alterations. However, since JAK2 first discovery in 2005, an increasing number of patients with concomitant BCR::ABL1 rearrangement and JAK2 mutations have been reported, and in a recent comprehensive review of the literature, we identified 87 cases carrying both genetic abnormalities ( Zanelli et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our recent review analyzing BCR::ABL1/JAK2 V617F double-positive cases, the majority of patients fell into the group of JAK2 -mutated MPN preceding CML (49.42%) ( Zanelli et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation